Bionomics of Comadia redtenbacheri (Hammerschmidt, 1847) (Lepidoptera: Cossidae) - C. Llanderal-Cázares; R. Castro-Torres; K. Miranda-Perkins (SHILAP)
Boring insects feed on the internal tissues of their hosts, and their activity is detected only after a severe damage to the host has occurred; therefore, studying their biology in the wild is difficult. The objective of the study was to complement knowledge about the biology, ecology and taxonomic position of Comadia redtenbacheri (Hammerschmidt, 1847), an agave borer with a long lifecycle. Laboratory observations were made on life stages obtained from larvae collected in Hidalgo, Mexico, which were induced to pupate in tubes with vermiculite and soil. Emerged adults were placed in cloth bags where they mated and laid eggs. Larvae that emerged from these eggs were raised on an artificial diet. Field observations were made in some localities of the State of Mexico; for this, external leaves and rhizomes of Agave plants were examined to look for eggs and larvae. Eggs and larvae were found in Agave salmiana Otto ex Salm-Dyck and Agave applanata Lem. ex Jacobi. Eggs are brown; they are found mainly at the base of external leaves. Neonate larvae bore a hole in the chorion and feed on it for a few days; they are gregarious and migrate towards the rhizome as they mature; last instar larvae are aposematic and release a volatile odoriferous secretion; their development is not uniform and can last more than a year. Pupation takes place in a silken cocoon under the soil. Adults are nocturnal; female calling starts one hour after the start of the scotophase, and can last until 5:30 am; oviposition happens a few hours after mating. The parasitoids Lisonnota fascipennis Townes, 1978 (Hymenoptera: Ichneumonidae), and Acantholespesia texana (Aldrich & Webber, 1924) (Diptera: Tachinidae) and fungal and bacterial pathogens are commonly found in larvae. Predators of larvae and adults include ants, rodents and birds.